Determinants of international tourism in Malaysia: evidence from gravity model - Ahmad Kosnan, Siti Shuhada; Ismail, Normaz Wana; Kaliappan, Shivee Ranjanee (Fakulti Ekonomi dan Pengurusan, Universiti Kebangsaan Malaysia, 2013)
The present study uses the Gravity type approach for panel data spanning from 1998 to 2009 to identify demand and supply factors in the Malaysian tourism industry. The findings reveal that the market size for both destination and source countries, country that share common border and common language with Malaysia are major factors that increases inbound international tourist and thus increase the tourist receiptin Malaysia. On the other hand, shorter distance and lower transportation costs also attract more tourists. The role of the exchange rate and the cost of living are equally important, as the depreciation of the Ringgit Malaysia (RM) and the lower cost of living attract more tourists to Malaysia. Alongside demand factors, the present study also examines supply factors, such as room availability and various components of infrastructure. The number of hotel rooms; quality in road infrastructure; and air transport infrastructure appear to be an important factor among international tourists.